2012
DOI: 10.1680/macr.11.00012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of slab bottom reinforcement on seismic performance of post-tensioned flat plate frames

Abstract: Young-Mi ParkChief Engineer, Doosan Engineering and Construction Company, South KoreaThe purpose of this study is to evaluate the seismic performance of gravity-designed post-tensioned flat plate frames with and without slab bottom reinforcement passing through the column. In low and moderate seismic regions, the seismic demands may not control the design, and buildings are often designed considering only gravity loads. This study focuses on the seismic performance of gravity load designed post-tensioned flat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Equations 1-3 do not account for the effect of flexural reinforcement. Although it has been reported that slab flexural reinforcement strongly affects the punching shear strength and the failure mechanism (Han et al, 2012;Sagaseta et al, 2011), this study only considered the equations specified in ACI 318-11.…”
Section: Crack Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Equations 1-3 do not account for the effect of flexural reinforcement. Although it has been reported that slab flexural reinforcement strongly affects the punching shear strength and the failure mechanism (Han et al, 2012;Sagaseta et al, 2011), this study only considered the equations specified in ACI 318-11.…”
Section: Crack Patternsmentioning
confidence: 99%
“…Numerous research studies have been conducted to evaluate the punching shear strength of solid flat slabs (Elstner and Hognestad, 1956;Han et al, 2006Han et al, , 2012Hawkins et al, 1974;Hueste and Wight, 1999;Islam and Park, 1976;Kang and Wallace, 2005;Kinnunen and Nylander, 1960;Pan and Moehle, 1992;Rodrigues, 2012;Sagaseta et al, 2011), but research on evaluating the punching shear strength of voided flat slabs is limited (Aldejohann and Schnellenbach-Held, 2003;Schnellenbach-Held and Pfeffer, 2002). So far, research regarding the punching shear strength of voided transfer slabs with small l/d has not been reported.…”
Section: Introductionmentioning
confidence: 99%